Chava Rosenfarb: The Yiddish Woman Writer in the Post-Holocaust World - Morgentaler, Goldie (Canadian Jewish Studies / Études juives canadiennes, 2003)
Chava Rosenfarb has been considered one of the great Yiddishwriters of her generation. But because she has written primarilyin Yiddish, her name and work are hardly known to English-speakingreaders, despite the fact that she has lived inCanada for over 50 years. This essay gives an overview ofRosenfarb’s life and career, suggesting that it is as a Yiddishwriter rather than as a woman that Rosenfarb has felt mostdiscriminated against.